`But having someone, kind of, walk you through what to do…`: exploring women athletes` preferences for learning and practicing self-compassion - Johnson, K. L.; Adam, M. E. K.; Kowalski, K. C.; Mosewich, A. D.; Schellenberg, B. J. I.; Storey, K. E.; Ferguson, L. J. (Qualitative Research in Sport, Exercise and Health, 2025)
Women face a variety of challenges as athletes, many of which are rooted in the gendered nature of sport. Despite these challenges, they have the potential to thrive in sport provided they have access to appropriate resources such as tailored mental performance programs focused on self-compassion. With the current sport psychology evidence base largely focused on sport experiences and program preferences of men athletes, current programs overlook the specific preferences of women athletes. Therefore, the purpose of this qualitative descriptive study was to explore competitive women athletes` preferences for learning and practicing self-compassion. Data were generated through focus groups. A total of 19 women athletes, from a variety of sports, took part in focus groups, discussing initial preferences for learning and practicing self-compassion. Focus group data were analysed with thematic analysis, and findings were presented as an infographic to participants for member reflection. A total of 11 women athletes returned for member reflections to help refine final themes. Two preferences in learning self-compassion were (1) multiple interactive professional-led group sessions and (2) sport-integrated progressive pre-season programming. Four preferences in practicing self-compassion were (1) setting self-compassion goals before sport, (2) managing self-talk during sport, (3) compassionately reflecting on performance after sport, and (4) access to support people. A final preference, relevant to both learning and practicing self-compassion, was variety in accessible self-compassion-based resources. The current study advances the sport psychology literature by amplifying women athletes` voices, who continue to call for greater support from the larger sport system.